TIPOLOGI DAN MORFOLOGI KAWASAN KOTA LAMA SEMARANG - Mandaka, Mutiawati; Huda, Ivan Syamsul; Yulitriani, Esti (ALUR :Jurnal Arsitektur, 2023)
The purpose of this paper is to determine the typology and morphology of the old city of Semarang. The method used is a literature review with a focus on scoping reviews to explain the typology and morphology of an area. The old city of Semarang was appointed as the research theme by taking into account the history and uniqueness that has a very strong character. The results showed that the old city of Semarang was formed from a square-shaped city framework consisting of roads, plots and buildings where there were urban artifacts in it from a fairly long process based on the formation of the city geographically and if viewed from its history.